Novel Mutations Related with Von Willebrand Disease in Iraqi Patients - Ali H. AL-Musawi (Journal of Global Pharma Technology, 2017)
Von Willebrand Disease (VWD) is the most common hereditary bleeding disorder in humans, with an estimated prevalence ranging upward to 1% of the general population. Males and females are both approximately equally affected. VWD arises from a deficiency or dysfunction of von Willebrand factor (VWF). The aim of this study was to detection of mutations of VWF gene in 15 unrelated patients. Polymerase chain reaction (PCR) and direct sequencing was performed for two functionally regions of the gene (exon 18 and exon 19). This study showed many mutations occurred in males and females patients that is impact  for the change  arrangement the amino acid  causing change VWF protein (as a carrier and protection of F8 protein responsibility for hemophilia A)function, and leading to Von willebrand disease. This study showed several mutations within the VWF gene in fifteen Iraqi patients by the molecular analysis revealed 35 point mutations in this study. These mutations included 15 missense variant and 9 silent mutations, while the rest were intrinsic mutations .These mutations may be related with   Von willebrand disease.Keywords: Von willebrand, Mutation, PCR.